Nanotechnology In Temporary Anchorage Devices - X, Chelza; Sivadasa, Anand (Orthodontic Journal of Nepal, 2022)
Introduction: Nanotechnology is the technique of manipulating matter at nano level. It has assured promising results in many fields of medicine including dentistry. There has been a wide range of application for nano particles in orthodontics, periodontics and also in prosthetic dentistry. Nano particle incorporated biomaterials has given promising results in many disciples of orthodontics. Nanoparticle coated brackets, arch wires and ligatures have assured promising results in revolutionising the orthodontic treatment mechanics. Temporary anchorage devices are one of the recent inventions which has revolutionised the orthodontic field. They are known to provide efficient means of anchorage and also support different types of tooth movements making them less complicated, although they may be associated with infections in the site of insertion and loss of stability. This article discusses the application of nano-particles in temporary anchorage devices, application of the same to reduce the incidence of peri-implantitis and loss of stability and the clinical evaluation of the same.